Pengaruh Investasi, Tenaga Kerja, dan Pembangunan Teknologi Informasi dan Komunikasi terhadap Pembangunan Ekonomi Inklusif di Kawasan Timur Indonesia dan Kawasan Barat Indonesia - Anggitaningrum, Aprilian; Iranto, Dicky; Nikensari, Sri Indah (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This research aims to see whether there is an influence of investment, labor, and information and communication technology development on Inclusive Economic Development in the Eastern Region of Indonesia and the Western Region of Indonesia. The research method used in this research is panel data from 2017-2021 in 13 provinces in the eastern region of Indonesia and 21 provinces in the western region of Indonesia. Data presented annually is obtained from the Central Statistics Agency, the Ministry of Investment of the Republic of Indonesia, and the National Development Planning Agency of the Republic of Indonesia. Based on the results of the partial analysis, the Investment variable has a positive and significant effect on Inclusive Economic Development in the Eastern Region of Indonesia seen from the probability value which is smaller than 0.05. Meanwhile, in the Western Region of Indonesia, the investment variable has no effect on inclusive economic development as seen from the probability value which is greater than 0.05. The labor variable has a positive and significant effect on inclusive economic development in the Eastern Region of Indonesia and the Western Region of Indonesia seen from the probability value which is smaller than 0.05. The information and communication technology development variable has a positive and significant influence on inclusive economic development in the Eastern Region of Indonesia and the Western Region of Indonesia as seen from the probability value which is smaller than 0.05. Simultaneously, all variables have a significant influence on inclusive economic development in the Eastern Region of Indonesia and have an influence of 93.07% and the remaining 6.03% is explained by other variables outside the research. Simultaneously, all variables have a significant influence on inclusive economic development in the Western Region of Indonesia and have an influence of 87.61% and the remaining 12.39% is explained by other variables outside the research.